The important value of mangrove crabs based on sediment conditions at the Asam-Asam river estuary of Tanah Laut regency. Issue 1 (February 2022) - Halang, B; Suhaili, A; Hani, R; Arianto,; Haekal, A F; Akbar, Z; Isnaeni, R
Abstract: Mangrove scabs ( Scylla ) are organisms that have very high commodity values and are satisfied by many communities in Indonesia, including communities at the Estuary of Asam-Asam River. This research aimed to analyze the important value index of mangrove crabs based on sediment conditions at the Estuary of Asam-Asam River in Tanah Laut Regency. The method of this research was the descriptive method with the direct observation to the field for defining the five sampling points. We took mangrove crab samples three times at each sampling point with distinct periods. The three sampling points lay at the river estuaries and two sample points lay at the non-river estuaries (about 100 meters to 200 meters from the estuary). The results showed that two species of mangrove crabs were found at the region of the river estuaries were Scylla serrata with the Important Value was 133, 33 dan Scylla paramamosain which the Important Value was 66, 67. Important Value Indexes of these mangroves were high and indicated that these mangrove crabs could play large important ecologic roles in their communities. The mangrove crabs which be found were very little because the condition of the texture of sediments were clays and the contents of air hardness of water were high (smallest 50, 8 mg/l) as well as Total Suspended Solid (smallest 55 mg/l) were a high concentration